Training Needs of Pig Farmers in Darjeeling Hills - Roy, Rakesh (Indian Journal of Hill Farming, 2016)
Assessment of training needs prior to commencement of training programmes and imparting knowledge according to the needs of the farmers makes the training more effective and meaningful. This paper deals with the objective to analyse the training needs of pig farmers in Darjeeling hills. The study was conducted by personally interviewing 120 respondents. The study shows that training need index (TNI) of the pig farmers was highest for animal healthcare management followed by feeding management and general management practices. The study also shows that use of antibiotic drugs during illness, preparation of low cost feed, special care to sow after furrowing, sign and symptoms of pregnancy were most preferred sub topic on animal healthcare management, feeding, general management and breeding management respectively. The study further shows that floor spacing requirement, preparation of value added meat product and knowledge about transmission of zoonotic diseases were most preferred sub topic on housing, marketing strategies and environment control respectively.